Effects of disulphide bonds between added whey protein aggregates and other milk components on the rheological properties of acidified milk model systems. (August 2016) - Liu, Guanchen; Jæger, Tanja C.; Lund, Marianne N.; Nielsen, Søren B.; Ray, Colin A.; Ipsen, Richard
Abstract: Micro- and nanoparticulated whey protein (MWP, NWP) were added to non-fat milk model systems and processed into chemically (glucono-delta-lactone) acidified milk gels. Model systems contained 5% protein in total and were made at two levels of casein (2.5% and 3.5%, w/w) with and without the thiol-blocking agent N-ethylmaleimide. The systems were characterised in terms of thiol groups, gel electrophoresis, particle size, and rheology during processing (homogenisation, heat treatment and acidification). The results showed that the formation of disulphide-linked structures in milk model systems was closely related to the increased particle size and rheological behaviour of the gels. MWP enriched systems produced, upon acidification, weak protein networks and required the addition of whey protein isolate (WPI) to increase gel strength. However, systems containing NWP exhibited pronounced increase in particle size and higher firmness of acidified gels through both covalent and non-covalent interactions.